Cytomegaloviruses : from molecular pathogenesis to intervention - Reddehase, Matthias J. (Matthias Johannes), 1954-; Lemmermann, Niels (Caister Academic Press, 2013)
Human Cytomegalovirus (CMV) - a member of the herpesvirus family - is an underrated health risk. A low public awareness results from the relatively mild symptoms it causes in otherwise healthy people whose immune systems are intact, with primary infection usually going unnoticed. During pregnancy, however, transmission from the mother to the fetus is currently the most frequent viral cause of birth defects with lifelong neurological sequelae, sensorineural hearing loss in particular. People at risk also include the growing number of immune compromised patients requiring either a solid organ gr.